eCM 2014
DOI: 10.22203/ecm.v028a11
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes: novel effectors of human platelet lysate activity

Abstract: Despite the popularity of platelet-rich plasma (PRP) and platelet lysate (PL) in orthopaedic practice, the mechanism of action and the effectiveness of these therapeutic tools are still controversial. So far, the activity of PRP and PL has been associated with different growth factors (GF) released during platelet degranulation. This study, for the first time, identifies exosomes, nanosized vesicles released in the extracellular compartment by a number of elements, including platelets, as one of the effectors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
194
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(211 citation statements)
references
References 113 publications
11
194
0
6
Order By: Relevance
“…Recently, it has been suggested that besides growth factors, extracellular vesicles (EVs), including exosomes and microvesicles, may play a major role in cell-to-cell communication 19. PRP activity might also be due to the efficient intercellular communication of bioactive molecules, mediated by nanosized vesicles, identified as exosomes 17. Based on these considerations, the aim of this study was to investigate whether exosomes can be considered as effectors of PRP functions and to identify their related molecular mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it has been suggested that besides growth factors, extracellular vesicles (EVs), including exosomes and microvesicles, may play a major role in cell-to-cell communication 19. PRP activity might also be due to the efficient intercellular communication of bioactive molecules, mediated by nanosized vesicles, identified as exosomes 17. Based on these considerations, the aim of this study was to investigate whether exosomes can be considered as effectors of PRP functions and to identify their related molecular mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Besides these growth factors, stimulation of platelets also causes them to secrete a number of extracellular vesicles, including exosomes (40 to 100 nm in diameter) 17. In recent years, much interest has been devoted to exosomes 18, which act as carriers of bioactive proteins, mRNAs, and microRNAs 19 and are increasingly regarded as playing crucial roles in cell-cell 20 and platelet-cell communications 21.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High levels of these growth factors and small RNAs have also been found in exosomes in PL. Exosomes might therefore play an important role in the effect of PL and represent a delivery system for cell-free therapy strategies [11]. Jalowiec et al [8] showed that there is a positive correlation between the platelet concentration in thrombin activated platelet gel and the protein secretion and observed the highest release of growth factors within the first 4 h after gelification.…”
Section: Introductionmentioning
confidence: 99%
“…They are nanovesicles secreted by PBMC with bioactive lipid bilayer. Its functions vary according to their origin and type of expressed protein [51]. In general, exosomes are derived from B lymphocytes that present MHC complex molecules, and they are able to present antigens to CD4 + T lymphocytes.…”
Section: Contributions For Classification Of Prp -Proposal Of a New Cmentioning
confidence: 99%